Permasalahan Pembelajaran IPS Mengenai Minimnya Pemahaman Tentang Isu Globalisasi - Selvi Agustin; Yulia Widya Saputri; Bagus Setiawan (Universitas 45 Surabaya, 2024)
Social studies learning problems related to the lack of understanding of globalization issues are a challenge for educators in developing appropriate curriculum and learning strategies. Globalization has a very dominant influence in various aspects, including in the field of social studies. Global issues such as the economy, health, security issues, outlook on life, human rights, poverty, etc. need to be taken into consideration in social studies learning. Social studies learning must be able to relate the subject matter not only to the school environment, but also to the global environment. Therefore, social studies learning must be responsive and organize itself in the face of globalization. Social studies learning with a global perspective can help students prepare themselves to face the future and deal with existing global problems. Appropriate learning strategies are highly expected in social studies learning so that students can understand global issues well.